2005
DOI: 10.1002/ijc.21421
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor–regulated ovarian cancer invasion and migration involves expression and activation of matrix metalloproteinases

Abstract: Vascular endothelial growth factor (VEGF) expression is elevated in primary ovarian tumors and metastases. We examined the effect of VEGF on epithelial ovarian cancer (EOC) in vitro invasion and migration and underlying mechanisms. Using the Matrigel invasion assay and colloidal gold phagokinetic track assay, we found that VEGF induced EOC DOV13 invasion and migration in a matrix metalloproteinase (MMP)-dependent manner. Using Western blotting, we show that VEGF, at 20-80 ng/ml, induced secretion of pro-MMP-7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 46 publications
1
51
0
1
Order By: Relevance
“…We have previously shown that MMP-7 is overexpressed in the invasive front of EOC and promotes invasion. MMP-7 secretion is increased by vascular endothelial growth factor and IL-8, which are mediators of LPA-induced EOC cell motility and invasion (17,44,51), suggesting a role of MMP-7 in the LPA-induced EOC metastasis. In the present study, we clarified the role of MMP-7 in EOC by sense and antisense MMP-7 gene transfection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that MMP-7 is overexpressed in the invasive front of EOC and promotes invasion. MMP-7 secretion is increased by vascular endothelial growth factor and IL-8, which are mediators of LPA-induced EOC cell motility and invasion (17,44,51), suggesting a role of MMP-7 in the LPA-induced EOC metastasis. In the present study, we clarified the role of MMP-7 in EOC by sense and antisense MMP-7 gene transfection.…”
Section: Discussionmentioning
confidence: 99%
“…Total MMP-7 concentration in DOV13 conditioned medium was determined by Quantikine ELISA kit (R&D Systems, Inc., Minneapolis, MN) as described previously (44). All assays were done in triplicate.…”
Section: Elisa and Gelatin Zymographymentioning
confidence: 99%
See 3 more Smart Citations